BODIPYs bearing a dimethylaminopropoxy substituent for imaging and photodynamic inactivation of bacteria - Palacios, Yohana Belén (2020)
A new BODIPY (BDP 1) bearing a dimethylaminopropoxy group attached to a phenylene unit was synthesized. This compound was brominated to obtain the halogenated analog BDP 2, which was designed to enhance the photodynamic effect of BODIPY to kill bacteria without an intrinsic cationic charge. The basic amino group located at the end of the propoxy bridge can acquire a positive charge by protonation in an aqueous medium, increasing the binding to bacterial cells. Interaction and photokilling activity mediated by these compounds was evaluated in Staphylococcus aureus and Escherichia coli. BDP 1 and BDP 2 were rapidly bound to bacterial cells, showing bioimages with green emission. Complete elimination of S. aureus was detected when cells were incubated with 1 μM BDP 2 and irradiated for 5 min. Comparable photoinactivation was obtained with E. coli, after an irradiation of 30 min. Furthermore, BDP 2 was effective to kill bacteria at very low concentration (0.5 μM). Thus, BDP 1 showed mainly interesting properties as a fluorophore, whereas BDP 2 was highly effective photosensitizer as a broad-spectrum antibacterial agent.